Embryonic day 9 yolk sac and intra-embryonic hemogenic endothelium independently generate a B-1 and marginal zone progenitor lacking B-2 potential - Momoko Yoshimoto; Encarnación Montecino-Rodriguez; Michael J. Ferkowicz; Prashanth Porayette; W. Christopher Shelley; Simon J. Conway; Kenneth Dorshkind; Mervin C. Yöder (2011)
The majority of B lymphocytes in the adult mouse are generated in the bone marrow from hematopoietic stem cells (HSCs) that first appear in the aorta-gonado-mesonephros region of the fetus on embryonic day (E) 10.5–11. Comparatively less is known about B-cell development during embryogenesis. For example, which specific embryonic tissues participate in B lymphopoiesis and whether hematopoietic differentiation is skewed toward specific B-cell subsets in the embryo are unanswered questions, because the systemic circulation is initiated early during embryogenesis, resulting in an admixture of cells potentially originating from multiple sites. We demonstrate, using Ncx1 −/− mice that lack systemic blood circulation, that the E9 yolk sac (YS) and the intra-embryonic para-aortic splanchnopleura (P-Sp) tissues independently give rise to AA4.1 + CD19 + B220 lo-neg B progenitor cells that preferentially differentiate into innate type B-1 and marginal zone (MZ) B cells but not into B-2 cells upon transplantation. We have further demonstrated that these B-1 progenitor cells arise directly from YS and P-Sp hemogenic endothelium. These results document the initial wave of innate B lymphopoietic progenitor cells available for seeding the fetal liver at E11. The results of these studies expand our knowledge of hemogenic endothelial sites specifying distinct B-1 and MZ cell fates apart from B-2 cells and independent of an HSC origin during development.